An Integrated Approach to Characterize Intestinal Metabolites of Four Phenylethanoid Glycosides and Intestinal Microbe-Mediated Antioxidant Activity Evaluation In Vitro Using UHPLC-Q-Exactive High-Resolution Mass Spectrometry and a 1,1-Diphenyl-2-picrylhydrazyl-Based Assay - Wang, Xiaoming; Chang, Xiaoyan; Luo, Xiaomei; Su, Meifeng; Xu, Rong; Chen, Jun; Ding, Yi; Shi, Yue (Frontiers in Pharmacology, 2019)
Intestinal bacteria have a significant role in metabolism and the pharmacologic actions of traditional Chinese medicine active ingredients. Phenylethanoid glycosides (PhGs), as typical phenolic natural products, possess wide bioactivities, but low oral bioavailability. The aim of this work was to elucidate the metabolic mechanism underlying PhGs in the intestinal tract and screen for more active metabolites. In this study, a rapid and reliable method using an effective post-acquisition approach based on advanced ultra-high-performance liquid chromatography (UHPLC) coupled with hybrid Quadrupole-Orbitrap high resolution mass spectrometry (Q-Exactive-HRMS) provided full MS and HCD MS2 data. Thermo Scientific™ Compound Discoverer™ software with a Fragment Ion Search (FISh) function in one single workflow was developed to investigate the intestinal microbial metabolism of four typical PhGs. Furthermore, antioxidant activity evaluation of PhGs and their related metabolites was simultaneously carried out in combination with a 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay to understand how intestinal microbiota transformations modulate biological activity and explore structure–activity relationships (SARs). As a result, 26 metabolites of poliumoside, 42 metabolites of echinacoside, 42 metabolites of tubuloside, and 46 metabolites of 2′-acetylacteoside were identified. Degradation, reduction, hydroxylation, acetylation, hydration, methylation, and sulfate conjugation were the major metabolic pathways of PhGs. Furthermore, the degraded metabolites with better bioavailability had potent antioxidant activity that could be attributed to the phenolic hydroxyl groups. These findings may enhance our understanding of the metabolism, pharmacologic actions, and real active forms of PhGs.